Volume 4: Heat Transfer; Electric Power; Industrial and Cogeneration 1992
DOI: 10.1115/92-gt-190
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer in Serpentine Flow Passages With Rotation

Abstract: Heat transfer characteristics of a three-pass serpentine flow passage with rotation is experimentally studied. The walls of the square flow passage are plated with thin stainless-steel foils through which electrical current is applied to generate heat. The local heat transfer performance on the four side walls of the three straight flow passages and two turning elbows are determined for both stationary and rotating cases. The through flow Reynolds, Rayleigh (centrifugal type) and Rotation numbers are varied. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…And rotation effect was more conspicuous in radially outward flow passage than inward flow passage. After Wagner et al's meaningful work, Yang et al [7] (Ro 6 0.042) and Mochizuki et al [8] (Ro 6 0.232) studied heat transfer in rotating multi-pass smooth square channel by copper plate heating method. They concluded that the flow exhibited strong three dimensional structures in the 180-deg bends and a significant enhancement in heat transfer performance could be observed at all sharp turns.…”
Section: Effects Of Rotation Numbermentioning
confidence: 99%
“…And rotation effect was more conspicuous in radially outward flow passage than inward flow passage. After Wagner et al's meaningful work, Yang et al [7] (Ro 6 0.042) and Mochizuki et al [8] (Ro 6 0.232) studied heat transfer in rotating multi-pass smooth square channel by copper plate heating method. They concluded that the flow exhibited strong three dimensional structures in the 180-deg bends and a significant enhancement in heat transfer performance could be observed at all sharp turns.…”
Section: Effects Of Rotation Numbermentioning
confidence: 99%
“…Results indicated that the 180-deg turn had positive effect on heat transfer in the turn and downstream. Yang et al (1992) [5] and Mochizuki et al (1994) [6] studied heat transfer in rotating multi-pass smooth square channels vie copper plate heating technique. They concluded that the flow exhibited strong three dimensional structure in the 180-deg bends and a significant enhancement in heat transfer performance could be observed at all sharp turns.…”
Section: Effect Of Geometrical Factorsmentioning
confidence: 99%
“…And thus, flow in rotating channels becomes extraordinary complicated and three-dimensional. Luckily, many investigations on rotating U-ducts have been published by many previous works over the past two decades [4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
mentioning
confidence: 99%
“…The pin-fin cooling channel The Jabob empirical formula and Grimision formula 28 are given as follows…”
Section: Cooling Channel With Ribsmentioning
confidence: 99%